Morphology of the ventral lobe of the prostate and seminal vesicles in an ethanol-drinking strain of rats (UChA and UChB) - Martinez, Francisco E. [UNESP]; Laura, I. A.; Martinez, M.; Padovani, C. R. [UNESP]; Bustos-Obregón, E. (My University, 2001)
Chronic alcoholism alters reproduction and therefore may be responsible for alterations of prostate and seminal vesicles, which are the subject of this analysis in UCh ethanol-drinking rats. The prostate and seminal vesicles of 20 animals were submitted to macroscopic, light microscopy, electron microscopy and morphometric analysis. The UCh rats showed atrophy of the epithelium and reduction of the weight of the prostate and seminal vesicle, liver hypertrophy and fat infiltration and alterations of the hypothalamus-pituitary axis. Ethanol induces changes in the weight and in the epithelium of prostate and seminal vesicles and hypothalamus-pituitary axis of UCh rats.
Keywords: Atrophy; Seminal vesicle; Ventral lobe prostate; alcohol; follitropin; luteinizing hormone; testosterone; alcoholism; animal; atrophy; blood; chemically induced disorder; drug effect; epithelium; image processing; kidney; liver; male; organ size; pathology; prostate disease; rat; rat strain; scanning electron microscopy; seminal vesicle; ultrastructure; Alcoholism; Animals; Epithelium; Ethanol; Follicle Stimulating Hormone; Image Processing, Computer-Assisted; Kidney; Liver; Luteinizing Hormone; Male; Microscopy, Electron, Scanning; Organ Size; Prostatic Diseases; Rats; Rats, Inbred Strains; Seminal Vesicles; Testosterone